The effect of nine sessions of mindfulness-acceptance-commitment on sport performance and attention in volleyball players - Cascante Rusenhack, Marcio Maciel (2016)
Purpose: To determine the effect of nine sessions of Mindfulness-Acceptance-Commitment (MCA) on fitness and attention in volleyball players. A secondary aim was to study the association between attention and performance in volleyball players. Methods: Participants were 18 volleyball players (mean age = 19.5 ± 5.3 yr.) randomly assigned to a control (CTRL) and an experimental (EXP) group. The EXP condition performed 9 sessions of MAC consisting of 30-min of meditation, 30-min Yoga exercises and 30-min of body scanning. The control group did not perform exercise. Dependent variables were measured before (pre-test) and after (post-test) the intervention. The Stroop Test was used to assess attention and physical fitness was measured by volleyball serve and attacking skills. Three mixed factorial 2 x 2 ANOVAs were used to analyze dependent variables attention and skill performance. Pearson correlation was used to determine attention scores change (Δ = post-test minus pre-test) association with skill performance change (Δ = post-test minus pre-test). Results: No significant ANOVA interactions were observed for physical volleyball skills (p > 0.05). ANOVA results indicated significant differences on attention scores in the CTRL (pre-test = 53.6 ± 7.8, post-test = 57.1 ± 6.8) and EXP (pre-test = 51.7 ± 5.6, post-test = 59.3 ± 4.0) groups (p < 0.05). Post hoc analysis indicated that mean post-test attention scores in the EXP group were significantly higher than in the CTRL group (p < 0.05). A significant correlation (r = 0.478, p < 0.05) was found between score changes in attacking volleyball skills (Δ = 26) and attention (Δ = 6.6) scores. Conclusions: Results from this study suggest that MAC is effective for improving attentional skills following nine sessions of 90 min. Attention might be used as an indicator of attacking skills in volleyball.